2009
DOI: 10.1364/oe.17.011543
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and high power terahertz pulse generation beyond excitation bandwidth limitation via χ^(2) cascaded processes in LiNbO_3

Abstract: We proposed a novel THz generation technique beyond the limitation of the input optical pulse width, based on phase modulation via cascaded chi((2)) process. When intense THz electric field generated by optical rectification lies in electro-optic (EO) crystal, emitted THz field gives phase modulation to the optical excitation pulse. The phase modulation causes excitation pulse narrowing and consequently gives rise to the enhancement of conversion efficiency and THz wave bandwidth broadening. We experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…This red-shift is characteristic of the THz generation process 24,26,53,54 , which occurs through difference-frequency mixing among the optical spectral components 34,53,55 and which can be cascaded through multiple difference-frequency steps, leading greater than 100% photon conversion efficiencies.…”
Section: B Thz Pulse Energy and Conversion Efficiencymentioning
confidence: 99%
“…This red-shift is characteristic of the THz generation process 24,26,53,54 , which occurs through difference-frequency mixing among the optical spectral components 34,53,55 and which can be cascaded through multiple difference-frequency steps, leading greater than 100% photon conversion efficiencies.…”
Section: B Thz Pulse Energy and Conversion Efficiencymentioning
confidence: 99%
“…Recent numerical and experimental studies [101,102,99] indicate the importance of the careful choice of the pump pulse duration. Nagai et al [102] observed enhanced THz generation at higher pump powers which was attributed to the shortening of the pump pulse due to phase modulation caused by the THz field.…”
Section: 3perspectives and Limitationsmentioning
confidence: 99%
“…Recent numerical and experimental studies [101,102,99] indicate the importance of the careful choice of the pump pulse duration. Nagai et al [102] observed enhanced THz generation at higher pump powers which was attributed to the shortening of the pump pulse due to phase modulation caused by the THz field. Based on numerical calculations [103] it is expected that THz peak electric field strengths on the 10 MV/cm scale can be generated from cryogenically cooled LN when longer (~500 fs) pump pulses are used rather than the commonly used~100 fs.…”
Section: 3perspectives and Limitationsmentioning
confidence: 99%
“…The most efficient generation method involves using a femtosecond laser to obtain Cherenkov radiation from lithium niobate (LN) [5][6][7][8][9]. LN has an intrinsically large second-order nonlinear susceptibility χ (2) , and is thus expected to generate intense THz pulse through the optical rectification (OR) process with broad-band femtosecond laser pulses.…”
Section: Intense Single-cycle Thz Pulse Generationmentioning
confidence: 99%
“…The inset shows THz intensity image measured at the focused point after the last off-axis parabolic mirror (PM3 in Fig. 1) [7].…”
Section: Intense Single-cycle Thz Pulse Generationmentioning
confidence: 99%